A catalogue of the Chrysididae (Insecta, Hymenoptera) types deposited in the Zoological Museum, Moscow Lomonosov State University, Russia - Rosa, Paolo; Antropov, Alexander V.; Xu, Zaifu (Zootaxa, 2015)
A critical and annotated catalogue of 52 types of Chrysididae belonging to 32 species deposited in the Zoological Museum of Moscow Lomonosov State University is given. The lectotypes of Chrysis sabulosa Radoszkowski, 1877 and Ellampus (Philoctetes) fedtschenkoi Semenov, 1932 are designated. New synonyms are proposed for (valid name first): Omalus imbecillus (Mocsáry, 1889) = Ellampus kozhevnikovi Semenov, 1932, syn. nov., and Chrysis speciosa Radoszkowski, 1877 = C. fulvicornis Mocsáry, 1889, syn. nov. The status of Hedychridium erschovi (Radoszkowski, 1877), stat. resurr. is revalidated.